1999
DOI: 10.1038/sj.jhh.1000839
|View full text |Cite
|
Sign up to set email alerts
|

Reduced production of nitric oxide during haemodialysis

Abstract: Objective: To examine the influence of systemic nitric oxide (NO) synthesis on blood pressure in patients with chronic renal failure undergoing haemodialysis, since nitric oxides are susceptible to renal excretion or are dialysed, a different indicator that is unaffected by renal function, such as the level of exhaled NO was evaluated. We examined the levels of the endogenous NO before and after a haemodialysis session. Design and methods: We evaluated the serum concentrations of nitrite/nitrate and the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Recently, a seasonal variation in plasma NO was reported with lowest levels occurring in the months of January and February (McLaren et al, 2000). The NO levels of healthy subjects studied in the months of February and May are in agreement with normal levels reported by other investigators: 28.9 AE 3.6 (Ochoa et al, 1991); 25.6 AE 10.3 (Yamamoto et al, 1998); 42 AE 17 (Sumimo et al, 1999);39.5 AE 19.4 (Gucuyener et al, 2000); and 33 AE 6 for males and 16.3 AE 3 (Taskiran et al, 2000) mM for females. The method of population multiple-component analysis requires that certain conditions be met regarding minimum sample size and minimum sampling rate (Fernandez and Hermida, 1998).…”
Section: Reprintssupporting
confidence: 89%
“…Recently, a seasonal variation in plasma NO was reported with lowest levels occurring in the months of January and February (McLaren et al, 2000). The NO levels of healthy subjects studied in the months of February and May are in agreement with normal levels reported by other investigators: 28.9 AE 3.6 (Ochoa et al, 1991); 25.6 AE 10.3 (Yamamoto et al, 1998); 42 AE 17 (Sumimo et al, 1999);39.5 AE 19.4 (Gucuyener et al, 2000); and 33 AE 6 for males and 16.3 AE 3 (Taskiran et al, 2000) mM for females. The method of population multiple-component analysis requires that certain conditions be met regarding minimum sample size and minimum sampling rate (Fernandez and Hermida, 1998).…”
Section: Reprintssupporting
confidence: 89%
“…Although studies of systemic production of NO in CRF patients have yielded contradictory results, 4,[29][30][31][32] our findings that l-arginine transport is increased in erythrocytes may reflect a broad activation of the l-arginine-NO pathway in cells of patients with CRF. Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Nonetheless, research has suggested a possible association of increased NO metabolite concentrations in plasma with enhanced NO production and decreased renal function (25). The concentration of NO 2 − plus NO 3 − in serum has been observed to decrease more than either blood urea nitrogen (BUN) or creatinine following dialysis, and the concentrations of these 2 analytes have been suggested as a potential indicator of renal impairment (26). Similar associations of NO 3 − concentrations have been observed in pre- and postdialysis plasma (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similar associations of NO 3 − concentrations have been observed in pre- and postdialysis plasma (27). Because salivary NO 3 − is reduced to NO 2 − by bacteria in the oral cavity (28) and because both NO 3 − and NO 2 − are removed from the blood by dialysis (26), salivary NO 2 − has also been selected as a suitable candidate marker for monitoring dialysis efficacy.…”
Section: Discussionmentioning
confidence: 99%